(Et il la regardait.) Un destin entre parenthèses - Jean-Marie Privat (Flaubert: Revue Critique et Génétique)
The ethnocriticism analysis of a group of parentheses in Madame Bovary highlights the role typographic discursive space and language imaginaries play in Flaubert’s writing. This study offers an intensive micro-reading of five micro-examples where appear in turn in/by the stylistic play of parentheses: narrative and cultural belligerence, semiotic and political intersigns encoding, esthetical deconstruction of social discourse, humoristic iconisation of graphic madness, dialogic interlocution with the reader and finally, the eroticization and aestheticization of punctuative curves. To conclude, this contribution emphasizes the topic dimension (not only temporal) of the parenthetical device and its poetic affinities with the “auratic”.